How images are conversed on twitter?. Issue 1 (2013) - Yoon, JungWon; Chung, EunKyung
Abstract: In a way of understanding how people communicate with others through images on Twitter, 174 Boston Bombing related tweet messages with images were analyzed to identify the characteristics of tweet message, senders, and influential tweet messages. According to the coding schemes on tweet messages, image uses, and senders, several features were demonstrated. People tweet primarily to express their opinions, share information, and report news. Images in those tweets were used differently depending on the categories of tweet messages. Major types of tweet senders were media and individuals, different categories of tweeter messages were found depending on types of tweeter senders. In addition, whether tweets are influential (highly retweeted) or not shows different patterns in terms of tweet message categories and senders.